2009
DOI: 10.1007/s10522-009-9240-4
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset dietary restriction compensates for age-related increase in oxidative stress and alterations of HSP 70 and synapsin1 protein levels in male Wistar rats

Abstract: Numerous reports implicate increased oxidative stress in the functional and structural changes occurring in the brain and other organs as a part of the normal aging process. Dietary restriction (DR) has long been shown to be life-prolonging intervention in several species. This study was aimed to assess the potential efficacy of late-onset short term DR when initiated in 21 months old male wistar rats for 3 months on the antioxidant defense system and lipid peroxidation, cellular stress response protein HSP 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 80 publications
3
19
0
Order By: Relevance
“…Therefore, the effect of the energetic restriction may be even higher than observed in this study. Our results and the previous examples show that HSP synthesis and activity are energetically costly; however, the processes of degrading a misfolded protein and re-synthesizing another cost one thousand times more (Sharma et al 2010). Therefore, this cellular stress response is considered a key physiological adaptation (Sharma et al 2010, Morris et al 2013).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Therefore, the effect of the energetic restriction may be even higher than observed in this study. Our results and the previous examples show that HSP synthesis and activity are energetically costly; however, the processes of degrading a misfolded protein and re-synthesizing another cost one thousand times more (Sharma et al 2010). Therefore, this cellular stress response is considered a key physiological adaptation (Sharma et al 2010, Morris et al 2013).…”
Section: Discussionsupporting
confidence: 58%
“…Stress proteins play an important role in energydependent processes, such as protein translocation into cellular organelles (Beckmann et al 1990) and the binding and release of denatured proteins and short peptides to HSP70 (McKay et al 1994, Mayer & Bukau 2005. Recently, it was observed that under in vitro conditions, one Hsp70 molecule consumed 5 ATPs to unfold a single misfolded protein into an intermediate that, upon chaperone dissociation, spontaneously refolded to its native state (Sharma et al 2010). Thus, ATP is considered indispensable for correct HSP70 functioning (Morimoto 1993, Currie et al 1999.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LTMCR was shown to prevent age-related decrease of Hsp70 mRNA levels in the rat liver [58] and alveolar macrophages [59] following heat shock. Moreover, HSP70 is increased in the hippocampus and cerebral cortex of calorie-restricted old rats [60]. We also observed beneficial effects of LTMCR on genes encoding enzymes related to antioxidant defenses.…”
Section: Discussionmentioning
confidence: 71%
“…Aging decreases the activities of superoxide dismutase, catalase and glutathione and increased lipid peroxidation and 70 kilodalton heat shock protein (Hsp70) levels in the brain and also in peripheral organs such as the liver, kidneys and heart. (6) One of the markers of oxidative stress is malondialdehyde (MDA), which is a product of lipid peroxidation with mutagenic, cytotoxic, and carcinogenic properties, due to its inhibitory effect on antioxidant enzymes. Therefore, increased MDA concentration is frequently used as one of markers of disordered homeostasis and aging.…”
Section: Introductionmentioning
confidence: 99%